2022
DOI: 10.1186/s12966-022-01370-5
|View full text |Cite
|
Sign up to set email alerts
|

Are intentions to change, policy awareness, or health knowledge related to changes in dietary intake following a sugar-sweetened beverage tax in South Africa? A before-and-after study

Abstract: Background In April 2018, South Africa implemented the Health Promotion Levy (HPL), one of the first sugar-sweetened beverage (SSB) taxes to be based on each gram of sugar (beyond 4 g/100mL). The objectives of this study were to examine whether the psychological constructs tax awareness, SSB knowledge, SSB risk perception, and intentions to reduce SSB intake were associated with taxed beverage intake, whether they changed from pre- to post-tax, and whether they modified the effect of the HPL. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 50 publications
1
3
0
Order By: Relevance
“…In the present study, the marginal effect analysis revealed that a one-level increase in SSB awareness could increase the probability of supporting SSB taxes by 17%. Compared with other factors, increased SSB awareness could greatly promote tax support, which is consistent with the result of a study conducted in South Africa (33). Further research should be conducted on various aspects, including residents' attitudes, countermeasures by enterprises, tax effects, and tax systems, which would provide a basis for the formulation of relevant policies.…”
Section: Discussionsupporting
confidence: 78%
“…In the present study, the marginal effect analysis revealed that a one-level increase in SSB awareness could increase the probability of supporting SSB taxes by 17%. Compared with other factors, increased SSB awareness could greatly promote tax support, which is consistent with the result of a study conducted in South Africa (33). Further research should be conducted on various aspects, including residents' attitudes, countermeasures by enterprises, tax effects, and tax systems, which would provide a basis for the formulation of relevant policies.…”
Section: Discussionsupporting
confidence: 78%
“…In South Africa where the government introduced the health promotion levy and a tax imposed on sugar to increase purchasing cost of SSB and discourage consumption, still citizens did not significantly reduce their demands. The study identified low awareness on the motives of the levy, and were influenced by addiction and branding effect to purchase SSB 36,37 . Moreover, implementation of taxation in sugar based on sugar content might counteract this effect 38 …”
Section: Economic Priorities Over Population Healthmentioning
confidence: 96%
“…The study identified low awareness on the motives of the levy, and were influenced by addiction and branding effect to purchase SSB. 36,37 Moreover, implementation of taxation in sugar based on sugar content might counteract this effect. 38 The introduction of taxation that can have a positive effect on the public health faces challenges due to the conflict of interest from government authorities and different globalization stakeholders.…”
Section: Economic Priorities Over Population Healthmentioning
confidence: 99%
See 1 more Smart Citation